Kebijakan Strategis Peningkatan Kapasitas Pasar Tradisional Dan Pedagang Kaki Lima Dengan Konsep Kemitraan Di Tangerang Selatan - Berlianingsih Kusumawati; Muchtar Riva’i; Ali Chaerudin (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
Presidential Regulation No. 112/2007 and Regulation of the Minister of Trade No. 53/2008 concerning the Arrangement and Development of Traditional Markets in Modern Market has been established. So along with the implementation of these regulations, then the rules to increase the capabilities and bargaining power of traditional traders, street vendors and entrepreneurs of modern markets is a strategic policy. The purpose of this study is to examine the concept of